Sustainable agricultural development compatible with environmental conservation in Asia (Japan international research center for agricultural science, 1998)
The proceeding recorded key speeches and disscussesat the workshop on main issues for sustainable agricultural development in Asia held on August 26 - 28, 1997, in Tsukuba Science City . The presents were devided into 3 section: Food problems in Asia; Agriculture and environment in Asia; and Technological issues after the Green Revolution